Implementation of Guidance and Counseling Techniques in Kindergarten - Badriyah, Lailatul; Putri, Ayu Aprilia Pangestu; Rafizah, Nur; Utami, Tiara Septia (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2025)
The purpose of this research is to describe how the implementation of Guidance and Counseling (BK) techniques is utilized at As-Sa'diah 1 Kindergarten in Samarinda City to support children in improving their socio-emotional development. This research employs qualitative methods, utilizing a case study approach. Data collection included observations, semi-structured interviews, and analysis of psychological test documents. The research findings indicate that the head of the institution, teachers, and parents collaborate to implement various Guidance and Counseling techniques in this institution. As an inclusive institution, this organization implements parenting programs, psychological tests, and child development screenings through collaboration with professional institutions. The Guidance and Counseling techniques applied in this institution include singing, storytelling, role-playing, drawing, and playing. The research results show that this institution has implemented the principles, teachers have performed their roles, applied techniques, and conducted evaluations in providing Guidance and Counseling services. Although there are obstacles in its implementation, such as teachers not having the opportunity to develop competencies and not having a background in Guidance and Counseling education, this institution strives to seek new insights to provide optimal services through cooperation with professional institutions, collaboration with parents, and gathering information from the internet and educational videos on social media.